2005
DOI: 10.22358/jafs/67020/2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three non-linear models for describing Japanese quail growth curve

Abstract: This study has focused on the comparison of Richards, Gompertz and Logistic growth models (functions) for describing the growth characteristics of three meat-type lines of Japanese quail. The live body weight data of wild-type, doted-white and extended-brown quail lines over time were collected and fitted to the three non-linear equations. The prediction performance of the models was evaluated by statistical error tests: mean percentage error (MPE), mean bias error (MBE), root mean square error (RMSE), and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
5
9
1
Order By: Relevance
“…Overall, regardless of genotype, male chicken had higher adult body weights W f , lower maturing rates and reached the point of maximum growth later than female chicken. This finding is in agreement with the results of Narinc et al(2010) and Ali et al (2002) who reported that irrespective of genotype or the rearing system, male birds had higher adult body weights W f and lower maturing rates k. Such a negative correlation between W f and k could be expected (Mignon-Grasteau et al 2000) for the growth curves that have similar shape parameters because the rate of maturation together with the shape parameter determines the speed of the curve to reach the asymptotic body weight (Sezer and Tarhan 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, regardless of genotype, male chicken had higher adult body weights W f , lower maturing rates and reached the point of maximum growth later than female chicken. This finding is in agreement with the results of Narinc et al(2010) and Ali et al (2002) who reported that irrespective of genotype or the rearing system, male birds had higher adult body weights W f and lower maturing rates k. Such a negative correlation between W f and k could be expected (Mignon-Grasteau et al 2000) for the growth curves that have similar shape parameters because the rate of maturation together with the shape parameter determines the speed of the curve to reach the asymptotic body weight (Sezer and Tarhan 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Age and weight at the inflection point were estimated high for male populations in this study compared to the females. This extension of the acceleration time may also explain the increase in the estimated mature body weight W f for the males (Sezer and Tarhan 2005 (Knížetová et al 1991) but higher than the 44.4 days (Goliomytis et al 2003) and48.9 days (N'dri et al 2006) estimated for male broilers, label-type chickens and White Leghorns, respectively, which all however used the Gompertz model. Generally, purebreds and unselected populations take a relatively longer time to reach the point of maximum growth or inflection than broilers and random-bred chickens due to the different genetic constitutions (Goliomytis et al 2003).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is supposed that these marker genes do not affect the growth pattern in poultry (12), whereas the effect of the roux plumage color mutation on growth was reported by Minvielle et al (16). The results of several studies showed that selection of the growth function must be strainspecific (12,20). The present study was undertaken to compare growth patterns of quail strains using nonlinear functions.…”
mentioning
confidence: 99%